2017
DOI: 10.1136/bmjopen-2016-015455
|View full text |Cite
|
Sign up to set email alerts
|

What are the key contextual factors when preparing for successful implementation of assistive living technology in primary elderly care? A case study from Norway

Abstract: ObjectiveTo identify contextual factors at different organisational levels to guide the implementation of an assistive living technology intervention in Norwegian primary home care.DesignA single embedded case study design was carried out in an urban municipality in Western Norway to get an overview of key contextual factors from the municipality’s perspective.Data collection and analysisThe data collection was based on a triangulation of methods involving document analysis, semi-structured individual intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…It was also used as a means to demonstrate system complexity, through the interactions at the micro, meso and macro system levels [38,44,46,47,49,54,57,64,67,68,71], supporting the programme theory. Multiple interactions between different aspects of context were reported across the evidence, for example the influence of macro-level contexts on the micro system or the tensions and trade-offs between the two [38,43,49,52,53,57,60,63].…”
Section: Representations Of Context Within Improvement Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also used as a means to demonstrate system complexity, through the interactions at the micro, meso and macro system levels [38,44,46,47,49,54,57,64,67,68,71], supporting the programme theory. Multiple interactions between different aspects of context were reported across the evidence, for example the influence of macro-level contexts on the micro system or the tensions and trade-offs between the two [38,43,49,52,53,57,60,63].…”
Section: Representations Of Context Within Improvement Settingsmentioning
confidence: 99%
“…Interactions between context and intervention were reported [54,68] and the interrelationship between intervention and context to achieve fit worked both ways: other studies reported on attempts to modify or 'improve' the local context prior to QI implementation in order to make it more supportive/receptive or to ameliorate the effects of contextual factors that impeded improvement efforts [48,51]. An example commonly mentioned was the alignment of national priorities to local work/improvement contexts or vice-versa [49,53,63]. However, misalignment of QI programme goals to local conditions/priorities, or an inability to achieve fit, was also highlighted [37,38,43,61,70] as a challenge when a mismatch between features of programme design/delivery and implementation contexts occurred.…”
Section: Managing Contextmentioning
confidence: 99%
“…It is about the economic use of all kinds of resources, together with managers that need to create a sustainable workplace for the healthcare professional, by providing enough learning and competence development and an attractive and interesting work. By being aware of the different motives of individuals related to healthcare work in municipalities, a higher success rate of using eHealth technologies can hopefully be obtained [13].…”
Section: Discussionmentioning
confidence: 99%
“…Even if the implementation of technology is on the agenda, the use of eHealth is not very well developed and the potential is far from exploited. Experiences from the use of eHealth so far show low success rates [13], and the interaction between technology and actors poses a major challenge [12].…”
Section: Introductionmentioning
confidence: 99%
“…Welfare technology raises ethical questions concerning security, reliability, confidentiality, legal obligations, technology acceptance, and adoption, among other issues (Sánchez, Taylor, and Bing-Jonsson 2017). While there is a governmental push to develop and implement technology to be used in eldercare, there are numerous unanswered ethical questions, as well as a lack of laws and regulation, national infrastructure, and standards (Garmann-Johnsen and Eikebrokk 2017, Gjestsen, Wiig, andTestad 2017, Pols 2017); this situation has a negative impact on the municipalities' manoeuvring spaces. The results of a Norwegian study on the implementation of assistive living technology in primary eldercare have shown that the lack of guidance from national authorities regarding financial, legal, and technological aspects had a negative impact on the uptake of new technologies (Gjestsen, Wiig, and Testad 2017).…”
Section: Shift In Responsibilitiesmentioning
confidence: 99%